2016
DOI: 10.1371/journal.pone.0163191
|View full text |Cite
|
Sign up to set email alerts
|

Purifying Selection, Density Blocking and Unnoticed Mitochondrial DNA Diversity in the Red Deer, Cervus elaphus

Abstract: The trajectories of postglacial range expansions, the occurrence of lineage patches and the formation and maintenance of secondary contact between lineages may mostly reflect neutral demographic processes, including density blocking, that may leave long-lasting genetic signatures. However, a few studies have recently shown that climate may also play a role. We used red deer, a large, mobile herbivore that is assumed to be sensitive to climate change, to test hypotheses of possible selection on the mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
(93 reference statements)
2
10
0
Order By: Relevance
“…3 ). The most recent study including Mesola red deer 56 found them to be highly divergent (as in the present study) and to be closely related to a rare haplotype found in the Polish Carpathians. This “Mesola lineage”, as the authors dubbed it, is in all likelihood identical to our haplogroup D and would thus include the Mesola deer, at least some maternal lineages in Eastern Europe and possibly C .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…3 ). The most recent study including Mesola red deer 56 found them to be highly divergent (as in the present study) and to be closely related to a rare haplotype found in the Polish Carpathians. This “Mesola lineage”, as the authors dubbed it, is in all likelihood identical to our haplogroup D and would thus include the Mesola deer, at least some maternal lineages in Eastern Europe and possibly C .…”
Section: Discussionsupporting
confidence: 80%
“…e . maral , the Mesola lineage 56 would turn out to be identical to what in the first large-scale phylogeographic study of red deer was called the Middle-Eastern lineage 4 or haplogroup D (present study).…”
Section: Discussionmentioning
confidence: 55%
“…These findings are corroborated in the network(Figure 3): the maral haplotypes from Turkey and the Caucasus are highly genetically diverse, falling far from the main Western/Central European cluster, but group with the Italian samples from the southern Apennines and Mesola. The latter were recently suggested as a separate subspecies, C. e. italicus, byZachos, Mattioli, Ferretti, and Lorenzini (2014), and their mitochondrial relationship to marals has been supported based on fossil and molecular evidence(Borowski et al, 2016;Croitor & Cojocaru, 2016). C. e. maral distantly connects Western Asian and European deer to the Central Asian subspecies (C. h. yarkandensis, bactrianus and hanglu) and to East Asian wapitoids(Figure 3).5 Central Asian elaphoids, C. h. bactrianus, yarkandensis and hanglu, together form a monophyletic clade, with bactrianus Rom.…”
mentioning
confidence: 98%
“…La Petite-Pierre). Based on 331 bp of d-loop AVd4 showed 100% similarity to red deer sequences from Poland (HQ534304, HQ534309, HQ534310, KX496902, KX496903, KX496905, KX496915) [ 69 , 70 ], and the Czech Republic (KM410131) [ 71 ].…”
Section: Resultsmentioning
confidence: 99%